Breast Cancer Risk in Users of Hormonal Contraception - Grabińska, Magdalena; Buda, Aleksandra; Halik, Paulina; Jusiak, Justyna; Pietrucha, Tomasz; Gołdyn, Mikołaj; Kubala, Karolina; Dudek, Adam; Zieliński, Daniel; Sędek, Małgorzata (Quality in Sport, 2026)
Combined oral contraceptives (COCs) are a widely used method of birth control among women. They have a low Pearl Index, confirming high efficacy. Their mechanism of action relies on suppression of ovulation. This is achieved through the influence of estrogenic and progestogenic components on the release of follicle-stimulating hormone and luteinizing hormone from the pituitary gland. COCs also inhibit fertilization by altering cervical mucus composition and prevent blastocyst implantation. The mechanism of action of COCs allows their use for non-contraceptive purposes. For example, they reduce the risk of ovarian and endometrial cancer. They also limit menstrual bleeding and alleviate acne, migraine headaches, and dysphoric symptoms. Conversely, adverse effects of COCs include an increased risk of cervical cancer. Their impact on breast cancer remains inconclusive. Clinical studies have demonstrated that the overall incidence of breast cancer among women using COCs is comparable to that among women who have never used them. However, during COC use and shortly after discontinuation, the risk of developing breast cancer is elevated, whereas it decreases five years after cessation. Among women with BRCA1 or BRCA2 mutations, the impact of COCs remains uncertain, with some studies reporting increased risk and others suggesting a reduction. Breast cancer is the most frequently diagnosed malignancy among women and the second leading cause of cancer-related death. Prognosis is often dependent on the stage at diagnosis. Mortality risk due to breast cancer is higher among women using COCs, whereas it does not significantly change with the use of progestin-only oral contraceptives. Some patients discontinue oral contraception due to concerns about adverse effects and a potential increase in breast cancer risk. The aim of this study was to present the mechanisms of COC action within breast tissue and their influence on the risk of breast cancer.